(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRAC This study aims to obtain empirical evidence whether there is an effect of the contribution of the BUMDes program on improving the welfare of the community in Mario Village, Libureng District, Bone Regency. This study uses a quantitative survey method approach by distributing questionnaires to 56 respondents consisting of BUMDes Manager Mario Pulana Mario Village and village communities who benefit from BUMDes itself. The collected questionnaires were analyzed using SPSS version 22. Beginning with testing the instrument, all statement items were valid and reliable. The data analysis method used: (1) basic assumption test (normality test); and (2) hypothesis testing consisting of: simple linear regression test and coefficient of determination. The results of the study stated that there was a positive and significant influence between the contribution of the BUMDes program to improving the welfare of the community in Mario Village, Libureng District, Bone Regency. Keywords: e-billing system, perceived ease of use, individual taxpayer